Investigating the impact of modified cassava starch with tannic acid and heat moisture treatment on physicochemical and in vitro starch digestibility - Mardiah Rahmadani; Rusli Fidriyanto; Nahrowi; Lilis Khotijah; Anuraga Jayanegara (Journal of Agriculture and Food Research, 2025)
Cassava starch, known for its high starch content, can be modified to increase resistant starch (RS), offering significant health benefits. This study aimed to investigate the dual modification of cassava starch using tannic acid (TA) and heat moisture treatment (HMT) to enhance its functional properties. TA, a polyphenolic compound, was applied at a concentration of 0.2 M either before or after HMT, and its effects on the physicochemical, thermal, and pasting properties, particle size, and in vitro digestibility of starch were evaluated. The results showed that TA, HMT, and the combined TA-HMT treatments significantly (p < 0.01) increased RS content and improved thermal properties. These modifications also significantly (p < 0.01) decreased the digestibility index of starch, rapidly digestible starch, and estimated glycaemic index (GI). Additionally, all treatments exhibited improved water-holding capacity, reduced crystallinity, and altered pasting behavior. However, the TA-HMT treatment resulted in the highest RS content and the lowest digestibility, making it more resistant to enzymatic breakdown. In conclusion, TA-HMT effectively modifies cassava starch, enhancing its nutritional profile by increasing RS and reducing GI. This makes it a promising ingredient for functional foods, supporting a sustainable approach to improving cassava starch for healthier dietary applications.